Spatial distribution of archeological sites in the Kingdom of Saudi Arabia and the application of the theory of planned behavior to predict pro-environmental behavioral intention among Saudi citizens - Nada Sulaiman Mohammed Alali; Tarek Abdel Azim Ahmed; Eman Sarhan Shaker (Humanities & Social Sciences Communications)
Abstract This paper aimed to investigate how awareness of negative consequences, subjective norms, attitudes, and perceived behavioral control dimensions influence pro-environmental behavioral intention to conserve four world heritage sites (Jeddah, Mada’in Saleh, Diriyah, and Jubbah) and to identify the spatial distribution of archeological sites in the Kingdom of Saudi Arabia. A self-administered questionnaire was used to collect data from a simple random sample of local residents in the four sites that was then subjected to multiple statistical analyses to test the hypotheses. Two thousand, three hundred, and forty-two local inhabitants responded to the two thousand, seven hundred, and fifty questionnaires that were delivered, accounting for a response rate of 85.1%, resulting in two thousand, two hundred, and ninety valid questionnaires for data analysis after closely examining the survey. Structural analysis revealed significant relationships within the adapted model, particularly in the context of heritage relics. The findings of PLS-SEM showed a positive influence of attitude, subjective norms, perceived behavioral control, and awareness of negative consequences on pro-environmental behavioral intention. In addition, the findings revealed that attitude significantly moderates the impact of awareness of negative consequences on pro-environmental behavioral intention.